The Weberian bureaucratic organization at the basis of the sociology of organizations - Chaouche, Hamid (Journal of Human Sciences, 2021)
In this paper, we have tried to understand how the Weberian theory of bureaucratic contribuated to the emergence of the sociology of organizations. We focused our analysis on the interest that this mode of organization constituted for the organizations which needed a rational organization of work in order to adapt to the important changes which they faced after the world war two. Through this analysis, we have discussed the most important characteristics of this mode of organization as well as the difficulties it raises when it is put into practice. Finally, we touched some theoretical and empirical studies having analyzed this question of bureaucracy which formed the theoretical and practical bases of the sociology of organizations, like the structuro-functionalism in the USA and the theory of strategic analysis, in France.